Analysis of the Impact of Product Quality, Price, and Brand Image on Purchase Decisions with Consumer Buying Interest as a Mediating Variable among iPhone Users in Yogyakarta - Heriputranto, Lukas Agung; Damanik, Ganda Wijaya; Kaloeti, Ade Kristianus (Jurnal Nasional Manajemen Pemasaran dan SDM, 2025)
This research investigates the impact of product quality, price, and brand image on purchase decisions, with consumer buying interest serving as a mediating variable, specifically among iPhone users in Yogyakarta. Employing a quantitative descriptive approach, data were gathered through questionnaires distributed to 100 respondents selected through purposive sampling. The analysis utilized various statistical tests, including Validity, Reliability, Convergent Validity, Discriminant Validity, AVE, Adjusted R², and F². The results indicate that Product Quality, Price, and Brand Image have a significant effect on Consumer Buying Interest. Nevertheless, these elements do not exert a direct positive influence on actual Purchase Decisions. The demographic profile of the respondents predominantly consisted of males aged 17–25, who were self-employed, possessed high school or diploma qualifications, and resided in Sleman. This study underscores the essential function of Consumer Buying Interest in connecting marketing elements (quality, price, brand image) with actual purchasing actions. It provides important implications for marketers and smartphone brands, suggesting that to enhance purchase rates, strategies should prioritize fostering consumer interest rather than relying solely on product characteristics.